The Child in Andalusian Poetry (The International Journal of Educational Sciences and Arts, 2026)
The child or childhood is one of the most important stages of human life. It increases its capacity to influence the different factors surrounding it, leaving an adult impact on its ingredients in all its stages. To study the child and its attention is one of the most important criteria that are measured by society and its development, and the number of children and its initiation is to meet the cultural challenges imposed by evolution, which evacuated this stage in many educational and social studies Environment and anatomical as psychologists, meeting and medicine see that childhood is the first phase of personal configuration and growth began from birth to puberty. I wanted to look at the child's theme in Andalusian poetry, this was an old heritage and he had to come to the present, as we needed rooting and adhering to the roots of heritage, and the artery of communication between the past and present.
Keywords: Child; Andalusian; Poetry